COMPUTERIZED ANALYSIS OF THE RELATIONSHIP BETWEEN ALLERGENICITY OF MICROORGANISMS AND THEIR HABITATS - A. O. Bragin; P. S. Demenkov; E. S. Tiys; R. Hofestädt; V. A. Ivanisenko; N. A. Kolchanov (Вавиловский журнал генетики и селекции)
The prevalence of allergic diseases was rapidly increasing in the 20th century. Currently, many people suffer from allergy in industrial countries. Therefore, analysis of allergenic properties of proteins is an urgent task. The following factors were formerly hypothesized to determine the allergenicity of a protein: size, enzymatic properties, and similarity to human proteins. However, no analysis of the relationship between allergenicity of proteins and the habitat of the organisms producing them has been conducted hitherto. We predict allergenicity of proteins from proteomes of more than 500 species of microorganisms. It is shown that the number of allergenic proteins in the proteomes of microorganisms is significantly associated with their pathogenicity, habitat, temperature conditions of the habitat, and oxygen demand.